2014
DOI: 10.1186/1471-2164-15-428
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of regulatory proteases sequences identified through bioinformatics data mining in Taenia solium

Abstract: BackgroundCysticercosis remains a major neglected tropical disease of humanity in many regions, especially in sub-Saharan Africa, Central America and elsewhere. Owing to the emerging drug resistance and the inability of current drugs to prevent re-infection, identification of novel vaccines and chemotherapeutic agents against Taenia solium and related helminth pathogens is a public health priority. The T. solium genome and the predicted proteome were reported recently, providing a wealth of information from wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 99 publications
0
3
0
Order By: Relevance
“…In addition to caspases and cathepsins identified in the previous studies,Yan and his colleagues [150] identified other CPs in T. solium genome such as several members of sapiens (clan CA) including calpain, ubiquitinyl hydrolase-L1 and ubiquitin-specific peptidase 14 representing families C2, C12 and C19, respectively. The investigators discussed their findings and predicted the characters and roles played by CPs expression using phylogenetic analysis and with comparison with similar CPs detected in other helminths such as E. multilocularis, S. mansoni, and Caenorhabditis elegans as models for of different helminth' classes.…”
Section: Cestodes • T Solium: a Cp Was Detected In E/s Of T Soliummentioning
confidence: 88%
“…In addition to caspases and cathepsins identified in the previous studies,Yan and his colleagues [150] identified other CPs in T. solium genome such as several members of sapiens (clan CA) including calpain, ubiquitinyl hydrolase-L1 and ubiquitin-specific peptidase 14 representing families C2, C12 and C19, respectively. The investigators discussed their findings and predicted the characters and roles played by CPs expression using phylogenetic analysis and with comparison with similar CPs detected in other helminths such as E. multilocularis, S. mansoni, and Caenorhabditis elegans as models for of different helminth' classes.…”
Section: Cestodes • T Solium: a Cp Was Detected In E/s Of T Soliummentioning
confidence: 88%
“…Previously Yan et al reported the genome-wide analysis of regulatory proteases in Taenia solium genome [12]. However, in our study, an in silico search of both proteases and PIs together in chickpea genome was conducted.…”
Section: Introductionmentioning
confidence: 92%
“…The crystal structure of recombinant T. s o l i u m Cu/Zn-SOD was this organism's first reported protein structure. T. s o l i u m expresses cytosolic Cu, Zn superoxide dismutase, a 2-Cys peroxiredoxin, and two glutathione transferase isoforms, all proven to protect mice against cysticercosis [70]. Their presence throughout developmental and adult stages highlights the pivotal role of antioxidant enzymes in T. s o l i u m physiology, suggesting potential for novel drug development.…”
Section: Novel Treatment Approachesmentioning
confidence: 99%
“…Yan et al [70] conducted a study identifying 197 novel proteases in T. s o l i u m , belonging to 37 families [69,70]. These proteases were classified based on the active site amino acid residue into categories like aspartic, cysteine, serine, metallo-serine, and threonine proteases.…”
Section: Novel Treatment Approachesmentioning
confidence: 99%